Green Porno: An Analysis of Its Artistic, Political, and Educational Potential - Sandrino, Camile (Revista do Colóquio, 2025)
This article analyzes the Green Porno series, created and starring Isabella Rossellini, in light of contemporary art practices, emphasizing elements of interdisciplinarity, performance, and activism. The research adopts a qualitative and exploratory approach, based on the aesthetic and conceptual analysis of the series and on dialogue with theorists such as Silvio Zamboni, Richard Schechner, and Judith Butler, supported by Eni Puccinelli Orlandi’s Discourse Analysis. The work proposes to analyze the Green Porno series and its potential as didactic, critical, and above all artistic material, examining its articulation with elements of contemporary art such as the performative and discursive resources used by Rossellini. It concludes that Green Porno contributes to broadening the ways of understanding contemporary art as a space for reflection, experimentation, and cultural transformation.